Do mycorrhizas play a role in the growth and development of Parashorea densiflora sloot & SYM? - Lee, Su See (1987)
Parashorea densiflora Sloat & Sym. fruits were grown in forest soil, sterile soil and sterile soil + forest soil to see whether germination and production of mature leaves were dependent on the growth medium and formation of ectomycorrhizas. Fruits germinated within one and a half weeks in forest soil as compared to four weeks in sterile soil. Production of normal leaves occurred three to sixteen weeks after germination in forest soil but took considerably longer in sterile soil, some fruits still having not produced normal leaves after eighteen weeks. Roots of seedlings grown in all media were not mycorrhizal eighteen weeks after germination. Formation of ectomycorrhizas in P. densiflora probably occurs after normal leaf production and when the seedling is older.